Emerging role of lncRNA ELDR in development and cancer. (29th April 2021) - Sur, Subhayan; Ray, Ratna B.
Abstract : Whole‐genome sequencing and transcriptome analysis revealed more than 90% of the human genome transcribes noncoding RNAs including lncRNAs. From the beginning of the 21st century, lncRNAs have gained widespread attention as a new layer of regulation in biological processes. lncRNAs are > 200 nucleotides in size, transcribed by RNA polymerase II, and share many similarities with mRNAs. lncRNA interacts with DNA, RNA, protein, and miRNAs, thereby regulating many biological processes. In this review, we have focused mainly on LINC01156 [also known as the EGFR long non‐coding downstream RNA (ELDR) or Fabl] and its biological importance. ELDR is a newly identified lncRNA and first reported in a mouse model, but it has a human homolog. The human ELDR gene is closely localized downstream of epidermal growth factor receptor (EGFR) gene at chromosome 7 on the opposite strand. ELDR is highly expressed in neuronal stem cells and associated with neuronal differentiation and mouse brain development. ELDR is upregulated in head and neck cancer, suggesting its role as an oncogene and its importance in prognosis and therapy. Publicly available RNA‐seq data further support its oncogenic potential in different cancers. Here, we summarize all the aspects of ELDR in development and cancer, highlighting its future perspectives in the context of mechanism. Abstract : During development, ELDR is highly expressed in neural stem cells along with its interacting partner HuR and regulates neural differentiation. In oral cancer, ELDR induces expression of EGFR and Cyclin E1 either alone or with interacting partner ILF3 and facilitates tumor growth.